Caracterización de la comprensión lectora y producción textual de estudiantes con presunción de TDAH (2018)
This article reports the results of a study which aimed to answer to main objectives. The first to characterize the third grade students of basic education, who presented behavioral and academic difficulties, indicating the possible presence of ADHD characteristics, to be referred to professionals in neurology. The second was to describe the scriptural features and readers of these students. In this study, a mixed research methodology was used, with some quantitative and other qualitative processes; where two questionnaires were applied, one for parents and another for teachers, designed based on DSM-5 (from its acronym in Spanish). A reading and writing test was also applied.